2020
DOI: 10.1093/ehjci/jez319.689
|View full text |Cite
|
Sign up to set email alerts
|

1227 Risk stratification of patients with asymptomatic moderate mitral regurgitation: the prognostic value of left atrial strain

Abstract: Background In asymptomatic moderate mitral regurgitation (MR), the criteria for risk stratification are still uncertain. Therefore, in these patients, optimal time of surgery remains controversial. Purpose Our aim was to compare left atrial (LA) strain to other echocardiographic parameters for the prediction of cardiovascular (CV) events in patients with asymptomatic moderate MR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cameli at al. demonstrated a correlation between reduced LALS, reduced LA emptying velocity, and/or thrombus in patients with PsAF before ECV/CA [33] . Zhu et al suggested that decreased LA strain in the reservoir phase may become a useful tool for predicting LA appendage stasis in patients with AF [34] .…”
Section: Discussionmentioning
confidence: 91%
“…Cameli at al. demonstrated a correlation between reduced LALS, reduced LA emptying velocity, and/or thrombus in patients with PsAF before ECV/CA [33] . Zhu et al suggested that decreased LA strain in the reservoir phase may become a useful tool for predicting LA appendage stasis in patients with AF [34] .…”
Section: Discussionmentioning
confidence: 91%